2013
DOI: 10.1016/j.imbio.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine administration modifies leukocyte proliferation and cytokine production in murine tissues

Abstract: Methamphetamine (METH) is a potent and highly addictive central nervous system (CNS) stimulant. Additionally, METH adversely impacts immunological responses, which might contribute to the higher rate and more rapid progression of certain infections in drug abusers. However no studies have shown the impact of METH on inflammation within specific organs, cellular participation and cytokine production. Using a murine model of METH administration, we demonstrated that METH modifies, with variable degrees, leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 19 publications
(25 reference statements)
5
52
1
Order By: Relevance
“…Terfenadine (an antiallergy drug) causes thymocyte death through a mitochondrial pathway and results in a remarkable increase in DNA fragmentation and the activation of certain caspases in rats (Enomoto et al 2004;Pozzesi et al 2014). Methamphetamine administration in a rodent model promotes apoptosis through caspase-9 activation and diminishes the thymic cellularity (Fujikawa et al 2007;Peerzada et al 2013;Pozzesi et al 2014). Geldanamycin, a heat shock protein-90 inhibitor, which is usually used as an anti-cancer agent, can target several oncogenic signaling pathways simultaneously (Cortese et al 2013;Fukuyo et al 2010).…”
Section: Role Of Chemotherapy In Atimentioning
confidence: 99%
“…Terfenadine (an antiallergy drug) causes thymocyte death through a mitochondrial pathway and results in a remarkable increase in DNA fragmentation and the activation of certain caspases in rats (Enomoto et al 2004;Pozzesi et al 2014). Methamphetamine administration in a rodent model promotes apoptosis through caspase-9 activation and diminishes the thymic cellularity (Fujikawa et al 2007;Peerzada et al 2013;Pozzesi et al 2014). Geldanamycin, a heat shock protein-90 inhibitor, which is usually used as an anti-cancer agent, can target several oncogenic signaling pathways simultaneously (Cortese et al 2013;Fukuyo et al 2010).…”
Section: Role Of Chemotherapy In Atimentioning
confidence: 99%
“…A previous study (3) reported that the widest distribution and the highest uptake of MA in the human body occurred in the lungs, and that this may render the lungs vulnerable to infection, pulmonary hypertension and pulmonary edema (3,4). The long-lasting pulmonary toxic effects of MA have placed an increased burden on healthcare costs (5).…”
Section: Introductionmentioning
confidence: 99%
“…METH adversely impacts immunological responses, which might contribute to the higher rate and more rapid progression of certain infections in drug abusers. We recently demonstrated that METH administration modifies leukocyte proliferation and cytokine production in diverse murine tissues (7). Also, the highest uptake of the drug occurs in lung, and levels are intermediate in brain (8).…”
Section: Introductionmentioning
confidence: 99%